Tren Pariwisata Kesehatan (Health Tourism) Global: Tinjauan Literatur Sistematis Berbasis Bibliometrik dengan Pendekatan PRISMA - Fahmi Muhammad; Rahma Dhani; Jumiati jumiati (Departemen Pariwisata Universitas Negeri Padang, 2026)
Health tourism, encompassing medical tourism and wellness tourism, has grown rapidly and has attracted increasing scholarly attention, particularly after the COVID-19 pandemic. This study aims to map the trends, sources, and thematic patterns of global health-tourism research using a Systematic Literature Review guided by PRISMA. Bibliometric data were retrieved through Publish or Perish from the Scopus database, yielding 200 publication records from 2015–2025. Following the PRISMA identification, screening, and eligibility stages, 196 documents (164 journal articles, 11 review articles, 11 book chapters, 6 books, and 4 conference papers) were deemed eligible for analysis. The results show a significant increase in publications since 2020, peaking in 2023 (30 publications), with 7,539 cumulative citations and an average of 37.7 citations per document. Wen's (2021) article on the effects of COVID-19 on Chinese travelers' lifestyles is the most cited record (657 citations). Sustainability (Switzerland) and the International Journal of Spa and Wellness are the most productive sources. Thematic analysis identified six clusters: wellness-tourism experience and revisit intention, post-pandemic resilience, sustainable destination development, medical-tourism adoption factors in developing countries, conceptual and literature-review contributions, and the most recent (2022–2025) research on senior travelers and psychological well-being. All 49 references cited in this article originate from verified Scopus records and are accompanied by DOI links for independent verification. These findings offer a research roadmap and recommendations for future health-tourism studies, particularly for developing-country contexts such as Indonesia.